Negative investment in China: financing constraints and restructuring versus growth - Knight, J; Ding, S; Guariglia, A (University of Oxford, 2010)
This paper attempts to address a puzzle in China's investment pattern: despite high aggregate investment and remarkable economic growth, negative net investment is commonly found at the microeconomic level. Using a large firm-level dataset, we test three hypotheses to explain the existence and extent of negative investment in each ownership group: what we term the efficiency (or restructuring) hypothesis, the (lack of) financing hypothesis, and the (slow) growth hypothesis. Our panel data probit estimations shows that negative investment by state-owned firms can be explained mainly by inefficiency: owing to over-investment or mis-investment in the past, these firms have had to restructure and to get rid of obsolete capital in the face of increasing competition and hardening budgets. The financing explanation holds for private firms, which have had to divest in order to raise capital. However, rapid economic growth weighs against both effects in all types of firms, with a large impact for firms in the private and foreign sectors. A tobit model, estimated to examine the determinants of the amount of negative investment, yields similar conclusions.